Parametric Evaluation of Mechanical and Surface Characteristics in FDM-Based 3D Printing - Pain, Pritam; Bose, Goutam Kumar; Bairagi, Bipradas (Journal of Graphic Era University, 2026)
This study investigates the influence of key process parameters – printing speed, temperature, and layer height – on the performance characteristics of three widely used Fused Deposition Modelling (FDM) materials: polylactic acid (PLA), acrylonitrile butadiene styrene (ABS), and nylon. The primary objective is to optimise surface roughness, shear strength, and wear resistance using advanced modelling and optimisation techniques. An L9 orthogonal array was used to vary the process parameters in the experimental design systematically. Analysis of Variance (ANOVA) was conducted to identify the factors that significantly influence surface roughness, shear strength, and wear resistance. Regression analysis and signal-to-noise (S/N) ratio charts were employed to assess the impact of each parameter. An Artificial Neural Network (ANN) was trained on the experimental data to predict shear strength and wear resistance accurately. Finally, a Genetic Algorithm (GA) was applied for multi-objective optimisation to simultaneously minimise surface roughness and wear resistance while maximising shear strength. The ANN model exhibited excellent predictive performance, with R-values of 0.99687 for shear strength and 0.91182 for wear resistance. The best parametric combination – 30 mm/s printing speed, 230∘C temperature, and 0.1 mm layer height – yielded 114 MPa shear strength, 94 μm surface roughness, and 0.08 wear resistance. Nylon demonstrated the highest shear strength and wear resistance under specific process conditions, while PLA provided the lowest surface roughness at optimal settings. The integration of ANN and GA provides a robust framework for process optimisation in FDM. The findings offer a basis for developing adaptive control strategies and reducing post-processing costs, contributing to improved performance and manufacturability of 3d-printed components.